Spatiotemporal quantification of key environmental changes in Stok and Kang Yatze regions of Ladakh Himalaya, India. Issue 26 (13th December 2022) - Soheb, Mohd; Ramanathan, Alagappan; Bhardwaj, Anshuman; Sam, Lydia
Abstract: Tourism fuelled economic transformation of Ladakh region is bringing a change in demography and livelihood preferences leading to increased exploitation of scarce natural resources. In addition to the nerve centre of tourism-related activities (Leh city), rural hinterlands of Ladakh are also witnessing a stark transformation in land and resource use patterns. In this study, we quantified and assessed the changes in key environmental parameters of rural Ladakh between 1969 and 2020. We observed a decrease in glacier area, glacier volume and vegetation cover by approximately 19%, 13% and 14%, whereas built-up and lake area increased by approximately 238% and 122%, respectively. Simultaneously, local population of the region doubled while tourism footprint increased by approximately 620-folds. The study highlights the environmental changes happening at a higher rate in rural regions around Leh city. Therefore, need of the hour is to recognize the disruptive changes being brought in the traditional way of life and to devise strategies to reorient the development paradigm towards sustainable resource use and management.